GOVERNMENT EFFORTS TO REALISE EDUCATIONAL EQUITY THROUGH TEACHER REDISTRIBUTION AND DIGITAL INFRASTRUCTURE IMPROVEMENT: A LITERATURE REVIEW ON STRATEGIES AND CHALLENGES IN REDUCING URBAN AND RURAL EDUCATIONAL DISPARITIES IN INDONESIA - Novalia Rachmah; Indra Cahaya Tresna; Tommi (Indonesian Journal of Education (INJOE), 2025)
Educational equity in Indonesia still faces significant challenges, particularly regarding quality and access disparities between urban and rural areas. This study employs a literature review method to analyse the government's strategies in reducing these disparities through two main approaches: teacher redistribution and digital infrastructure improvement. The findings indicate that teacher redistribution programmes, such as the Frontline Teachers programme and the placement of civil servant teachers (PNS/PPPK), have improved the teacher-student ratio and brought qualified educators to remote areas. Meanwhile, strengthening digital infrastructure through the Palapa Ring project, school digitisation, and the provision of technological devices have opened up more equitable access to online learning. However, the implementation of these two efforts still faces challenges such as teacher resistance to placement in remote areas, limited supporting facilities, low digital literacy, and limitations in basic infrastructure such as electricity and internet connectivity. This study concludes that the success of educational equity requires integrated policy synergy, local government involvement, and support from various stakeholders to ensure the sustainability of the programme.